2010
DOI: 10.3346/jkms.2010.25.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Cefotetan versus Conventional Triple Antibiotic Prophylaxis in Elective Colorectal Cancer Surgery

Abstract: This study examined infectious outcomes in elective colorectal cancer surgery between cefotetan alone or conventional triple antibiotics. From January to December 2007, 461 consecutive primary colorectal cancer patients underwent elective surgery. Group A contained 225 patients who received conventional triple antibiotics (cephalosporin, aminoglycoside and metronidazole) for prophylaxis, and group B contained 236 patients who received cefotetan alone for prophylaxis. Treatment failure was defined as the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…the prophylactic administration of antibiotics is known to be useful in the prevention of wound infection, and broad-spectrum antibiotics are recommended immediately before colorectal surgery. 26,27 in the field of therapeutic endoscopy of the colon, this practice is still controversial. further efforts are needed to provide practice standards and guidelines for colorectal esD.…”
Section: Discussionmentioning
confidence: 98%
“…the prophylactic administration of antibiotics is known to be useful in the prevention of wound infection, and broad-spectrum antibiotics are recommended immediately before colorectal surgery. 26,27 in the field of therapeutic endoscopy of the colon, this practice is still controversial. further efforts are needed to provide practice standards and guidelines for colorectal esD.…”
Section: Discussionmentioning
confidence: 98%
“…About one-third of the colorectal specialists use their own prescriptions, such as third-generation cephalosporin and fluoroquinolone treatment. A recently published study by Jeong et al [26] reported that second-generation cephalosporin alone was as effective as a triple regimen composed of first-generation cephalosporin, metronidazole, and aminoglycoside for elective colorectal cancer surgery prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Cefotetan (CTT) disodium is a third-generation semisynthetic cephamycin antibiotic with a broad-spectrum of antibacterial activity and a favorable pharmacokinetic activity (Ward and Richards 1985). A long serum half-life and resistance to beta-lactamase hydrolysis have made cefotetan an attractive chemotherapeutic agent, and the results of clinical trials worldwide have demonstrated its efficacy in a wide variety of clinical situations (Martin et al 1994), especially used as a prophylaxis in abdominal and pelvic surgeries (de Lalla 2009;Mahmoud et al 2009;Jeong et al 2010). The National Surgical Infection Prevention Project (NSIPP) has recommended prophylactic cefotetan administration to prevent infections in colorectal surgery patients, and cefotetan is currently the most commonly prescribed prophylactic antimicrobial agent in the United States (Bratzler et al 2005).…”
Section: Introductionmentioning
confidence: 99%